Heteropolyacid-loaded MOF-derived mesoporous zirconia catalyst for chemical degradation of rhodamine B - Wang Jialu; Yu Rongfei; Li Zhenying; Yang Fen; Luo Linmin; Wang Dandan; Cheng Huan; Zhang Yutao; Zhang Qiuyun (Green Processing and Synthesis, 2023)
In this article, silicotungstic acid (STA)-loaded metal–organic framework (MOF)-derived composites (C-STA@ZrO2) were successfully synthesized by simple strategies. X-ray diffraction, Fourier transform infrared, scanning electron microscopy, energy-dispersive X-ray, N2 physisorption, UV-vis diffuse reflection spectroscopy, and X-ray photoelectron spectroscopy techniques were used to characterize the as-obtained composites. Intriguingly, C-STA@ZrO2 exhibits excellent photocatalytic performance, and rhodamine B (RhB) (40 mg·L−1) in water can be degraded to 93.9% after 120 min of irradiation. Moreover, various catalysts, catalyst dosage, and dye concentrations on RhB degradation were evaluated. Besides, the reusability of C-STA@ZrO2 was also investigated. This work may provide a new and significant guideline for exploring excellent performance of MOF-derived hybrid material for wastewater purification.